Mapping the preclinical to clinical evidence and development trajectory of the oncolytic virus talimogene laherparepvec (T-VEC): a systematic review. Issue 12 (2nd December 2019) - Lalu, Manoj; Leung, Garvin J; Dong, Yuan Yi; Montroy, Joshua; Butler, Claire; Auer, Rebecca C; Fergusson, Dean A
Abstract : Objective: This study aimed to conduct a systematic review of preclinical and clinical evidence to chart the successful trajectory of talimogene laherparepvec (T-VEC) from the bench to the clinic. Design: This study was a systematic review. The primary outcome of interest was the efficacy of treatment, determined by complete response. Abstract and full-text selection as well as data extraction were done by two independent reviewers. The Cochrane risk of bias tool was used to assess the risk of bias in studies. Setting: Embase, Embase Classic and OvidMedline were searched from inception until May 2016 to assess its development trajectory to approval in 2015. Participants: Preclinical and clinical controlled comparison studies, as well as observational studies. Interventions: T-VEC for the treatment of any malignancy. Results: 8852 records were screened and five preclinical (n=150 animals) and seven clinical studies (n=589 patients) were included. We saw large decreases in T-VEC's efficacy as studies moved from the laboratory to patients, and as studies became more methodologically rigorous. Preclinical studies reported complete regression rates up to 100% for injected tumours and 80% for contralateral tumours, while the highest degree of efficacy seen in the clinical setting was a 24% complete response rate, with one study experiencing a complete response rate of 0%. We were unable to reliably assess safety due to the lack of reporting, as well as the heterogeneity seen in adverse event definitions. All preclinical studies had high or unclear risk of bias, and all clinical studies were at a high risk of bias in at least one domain. Conclusions: Our findings illustrate that even successful biotherapeutics may not demonstrate a clear translational road map. This emphasises the need to consider increasing rigour and transparency along the translational pathway. PROSPERO registration number: CRD42016043541.